Factors affecting agricultural emissions in the Western Balkans: Panel data analysis - Brankov, Tatjana (Serbian Journal of Management, 2023)
Reducing agricultural emissions is one of the most important issues in global policy, which is becoming increasingly challenging as time goes on. To address this, our study explores the major determinants of agricultural emissions in the Western Balkans while considering gross domestic product (GDP), agriculture value added, trade, energy use in agriculture, and foreign direct investments (FDI). The empirical results based on panel data analysis showed that GDP does not have a significant impact on emissions. Agriculture value added has had a significant and negative impact on nitrous oxide emissions and a significant and positive impact on methane emissions. Trade has significantly negatively affected nitrous oxide and methane emissions, while energy consumption has had a significant and positive impact on nitrous oxide and methane emissions. FDI has had a significant and positive impact on methane emissions, while its effect on nitrous oxide emissions was not statistically significant. This article can serve as a basis for further research on the topic.